Small Scale Enterprises (SSES) on Employment Opportunities in Kabwohe Municipality. - Niwagaba, Innocent (Kabale University, 2023)
The topic of the study was Small Scale Enterprises on Employment Opportunities in Uganda: A Case Study of Kabwohe Municipality Shema District. The problem for this study was the high rate of Unemployment in Uganda amidst the existence of many small-scale enterprises. The objectives of the study were: to determine the growth level of employment in Kabwohe municipality; to establish the level of growth of SMES in Kabwohe and to establish the effects of SMES on Employment opportunities in Kabwohe municipality Sberna district. The researcher used quantitative and qualitative research approaches; which specifically consisted of descriptive co-relational design and cross-sectional design. The findings revealed the following: From the findings of the study, on respondents' background information the researcher concluded that the majority of respondents in this sample were in their early adulthood age, that is, 30-39 years, there are more males than females in Kabwohe municipality employed in these Enterprises, majority of individuals in Kabwohe municipality are generally not well educated; It can also be concluded that the effects of small scale enterprise on employment opportunities is significant at 05 percent because the probability value is less than 05 level of significance. The researcher recommended that the government should reduce the taxes that these small¬scak enterprises pay for more jobs to be created and research should also be conducted before establishing any enterprises and before acquiring any financial assistance. By doing these. the enterprises will grow and more jobs will be created in the long run.